SYSTEMATIZATION OF NURSING ASSISTANCE: DIFFICULTIES OF IMPLANTATION IN THE CLINICAL PRACTICE (Fiep Bulletin - online, 2014)
The systematization of nursing assistance (SNA) consists of a working method through which occurs the planning, the development and the organization of the nursing team work. Through the SNA it is possible to evaluate the given assistance. In 2009, the Resolution COFEN nº 358 revoked the Resolution 272/2002 establishing the implantation of the SNA in all healthcare units that provide nursing assistance. However, still nowadays this practice has not been effectively implanted in all units which provide nursing assistance for several reasons. The researched studies show three groups of situations that make it difficult the effective implantation of the SNA in the clinical practice, which are: unprepared professionals to perform the SNA; theincorrect operation of the SNA; and the precariousness of human and physical resources available in health institutions. Thinking about the contribution of the SNA for the nurse's role and benefits for the institution and for the patient, it was notice the importance of identifying the difficulties for the implantation of the SNA in an attempt to provide reflections about them.
Keywords: nursing; nursing process; nursing assistance.